Human rights in the Arab world : independent voices - Chase, Anthony Tirado; Hamzawy, Amr (Pennsylvania studies in human rights., 2006)
This is the first book in English that draws together the work of intellectuals at the forefront of research on the Arab region's key human rights issues. Its empirical and theoretical focus is on the historical and contemporary place of human rights in Arab politics and the obstacles to advancing rights in the region.